The Implications of Behaviorist Learning Theory on Arabic Language Learning - Isop Syafei; Ade Arip Ardiansyah; Dadan Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the behaviorism theory in Arabic language learning and its impact on the design, implementation, and evaluation of the learning process. Additionally, it highlights the advantages and limitations of behaviorism in the context of Arabic language education. The research employs a literature review method, involving the process of searching, selecting, evaluating, collecting, and analyzing data from various sources. This approach allows researchers to gain a deeper understanding and synthesize relevant findings. The study’s findings indicate that: First, behaviorism emphasizes observable behavior, the use of positive reinforcement, clear feedback, repetition, and the active role of teachers as facilitators. Second, in behaviorism-based instructional design, key aspects include structured objectives, a supportive learning environment, positive reinforcement, and repeated practice. Third, teachers serve as leaders, facilitators, and feedback providers, while students play an active role in the learning process. Fourth, evaluation in Arabic language learning is conducted through objective assessment, progress monitoring, and feedback provision. Fifth, although effective in shaping behavior, this theory has limitations in addressing cognitive aspects, intrinsic motivation, and individual differences.